EDUKASI HIPERTENSI DAN PENGUKURAN TEKANAN DARAH PADA LANSIA DI PANTI WREDA BUDI DHARMA KASIH - Putri Elviningsih Zendrato; Tophan Heri Wibowo; Roro Lintang Suryani (PT. Jurnal Center Indonesia Publisher, 2024)
Elderly or elderly is the final stage of life characterized by physiological changes that are increasingly declining, one of which is in cardiovascular disease. Hypertension is a chronic condition characterized by increased blood pressure on the walls of arterial blood vessels. Based on a pre-survey at Panti Wreda Budi Dharma Kasih, it was found that more than half of the elderly experienced hypertension due to a lack of elderly knowledge about hypertension. This community service activity aims to educate the elderly about hypertension and invite the elderly to have a good lifestyle. This activity was carried out at Panti Wreda Budi Dharma Kasih attended by 27 participants. The PKM method is carried out by checking the blood pressure of the elderly using a sphygmomanometer and stethoscope. Screening of PKM participants is elderly people with a minimum age of 60 years who can hear and see. The provision of education is carried out by lecture method using power points containing the definition of hypertension and elderly causative factors and ways to prevent hypertension, then a question and answer session is held. Data collection on the level of knowledge was carried out using pre-education and post-education questionnaires. The results of this activity show an increase in knowledge in the elderly after providing education for 3 meetings.